3 Listen up! Expanding the educational podcast network at the great ormond street hospital (GOSH) learning academy. (23rd February 2023) - Thomas, Rhian; Cooke, Sara; Forman, Emma; Karia, Shriti; Trifonova, Ivanina; Court, Owen; Nguyen, Kathy; Goldstein, Gabrielle; Ip, Emma; Brierley, Joe; Gan, Hoong-Wei; Lall, Abhimanu; et al.
Abstract : Background: Podcasts usually take the form of digital audio files which can be freely and easily broadcast to subscribers in series of instalments. In recent years there has been a boom in the popularity of medical education podcasts. The GOSH Learning Academy piloted the release of educational podcasts between 2020 and 2021, demonstrating significant interest and reach of the material produced. The Digital Learning team have worked to build on this strong foundation, using an evidence-based approach to design a network of podcasts. The aim of the network is to produce quality, accessible material intended to impart education and highlight the innovative work of staff across the institution. Methods: A literature review was undertaken to explore and appraise the published evidence evaluating podcasting in healthcare education. Thematic analysis identified four areas of interest to be further explored – access, format, quality, and impact. A team-based approach was used to identify areas for improvement in current processes. A new podcast host was acquired, and data assurance processes streamlined. Results: As of September 2022, 4 podcast shows have been produced with 55 episodes released. Since 2020, there have been over 8, 300 listens across the podcasts; with over 4, 700 of these listens recorded since relaunch in January 2022. Evidence-based practice has been applied to maximise educational value including tweaking formats and creating new podcasts for targeted audiences. Social media has been utilised to market podcasts and a new hub created for staff members on GOSH DEN. Discussion: Data continues to suggest that podcasts are a valued and accessible method to convey educational material. Using an evidence-based approach and drawing on the expertise within the GOSH Learning Academy has allowed growth in the number of listeners and to improve the educational value of material produced. Further work is required to obtain evaluation from listeners.